Checklist of library building design considerations - Sannwald, William W., (Chicago : ALA Editions, 2024)
"This new update of Sannwald's classic guide will help you stay prepared and organized for every phase of your library building design project from conception through the dedication ceremony"-- Building planning and architecture -- Building construction alternatives -- Library site selection -- Sustainable design -- General exterior considerations -- Interior organization of library buildings -- Compliance with ADA accessibility guidelines -- Telecommunications, electrical, and miscellaneous equipment -- Interior design and finishes -- Entrepreneurial and collaborative spaces -- Materials handling and storage : book stacks and shelving -- Building systems -- Safety and security -- Maintenance of library buildings and property -- Building construction process, change orders, occupancy, and post-occupancy evaluation -- Groundbreaking and dedication ceremonies. "This new update of Sannwald's classic guide will help you stay prepared and organized for every phase of your library building design project from conception through the dedication ceremony"--